Possible effects of royal jelly against neuronal injury in the hippocampus of ovariectomized rats with pentylenetetrazol-induced seizures: Role of luteinizing and follicle-stimulating hormones - Asma Momeni; Mohammad Reza Salahshoor; Mohammadreza Afarinesh; Cyrus Jalili (Avicenna Journal of Phytomedicine)
Objective: This study aimed to investigate the potential impact of royal jelly (RJ) on hippocampal neurons in an ovariectomized (OVX) rat model with pentylenetetrazol (PTZ)-induced seizures by assessing luteinizing (LH) and follicle-stimulating (FSH) hormones.Materials and Methods: Fifty-six female rats (n=7/group) were divided into groups receiving saline (CTL, OVX, RJ, and OVX-RJ) and those undergoing PTZ-induced seizures (PTZ, PTZ-OVX, PTZ-RJ, and PTZ-OVX-RJ). OVX rats underwent bilateral ovary removal, followed by a 15-day RJ treatment at 300 mg/kg. The seizure model commenced 24 hours after the final RJ dose. Serum LH and FSH levels were measured, and Golgi staining assessed hippocampal neuron morphology.Results: The RJ group exhibited elevated LH and FSH levels compared to CTL. However, the PTZ-RJ group showed no significant changes in these hormones relative to the PTZ and CTL groups. In OVX-RJ rats, LH and FSH levels decreased compared to the RJ group, while PTZ-OVX-RJ rats showed increased levels. Dendritic spines remained unchanged in both the RJ and PTZ-RJ groups compared to the CTL and PTZ groups, respectively. Notably, OVX-RJ exhibited reduced spines compared to the RJ group, while PTZ-OVX-RJ showed an increase.Conclusion: RJ may protect against estrogen deficiency and seizure-related adverse effects on hippocampal neurons in OVX rats, highlighting its potential as a beneficial dietary supplement.